2018
DOI: 10.1111/bjso.12302
|View full text |Cite
|
Sign up to set email alerts
|

System justification theory at 25: Evaluating a paradigm shift in psychology and looking towards the future

Abstract: Since first being proposed 25 years ago, system justification theory has become a paradigm‐shifting framework for understanding intergroup relations and political psychology. Based on the thesis that people are motivated to defend and bolster the societal status quo, system justification theory helps to explain varied phenomena, including resistance to change, outgroup favouritism, and other instances of false consciousness. This paper summarizes four tenets of the theory including the following: (1) anteceden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 107 publications
(138 reference statements)
2
52
0
1
Order By: Relevance
“…To these ends, Feygina, Jost, and Goldsmith () showed that “system‐sanctioned change” could motivate those who are high on system justification to support efforts to combat climate change. Although it may be rare for conservative social groups to promote progressive change, and thus questionable as to how often this type of scenario may occur in real‐world settings (see Osborne, Sengupta, & Sibley, ), the findings nevertheless point to social identity as a strong motivating factor in people's attitudes.…”
Section: Discussionmentioning
confidence: 88%
“…To these ends, Feygina, Jost, and Goldsmith () showed that “system‐sanctioned change” could motivate those who are high on system justification to support efforts to combat climate change. Although it may be rare for conservative social groups to promote progressive change, and thus questionable as to how often this type of scenario may occur in real‐world settings (see Osborne, Sengupta, & Sibley, ), the findings nevertheless point to social identity as a strong motivating factor in people's attitudes.…”
Section: Discussionmentioning
confidence: 88%
“…A conservative interpretation of our findings is that nationalism buffers white New Zealanders against feelings that their ethnic group is deprived. This in itself represents a novel contribution to the literature on the psychological function of political ideologies, adding to the cultural diversity of this literature (see Osborne, Sengupta, & Sibley, ). However, a broader interpretation is that the link between GRD and nationalism results from a general psychological process in which members of societally dominant groups buffer their subjective well‐being against perceived deprivation by clinging to beliefs about national superiority.…”
Section: Discussionmentioning
confidence: 89%
“…(The publisher tells us that the original article is the second most highly cited one in the journal's history, which is humbling and gratifying.) Two of the commentariesby Friesen, Laurin, Shepard, Gaucher, and Kay (2019) and Osborne, Sengupta, and Sibley (2019) are very favourable in their evaluation of the present state of theory and research on system justification processes. Both articles provide key insights about research in this area and suggest future directions that complement those mentioned in Jost's (2019) target article.…”
Section: Our Response To the Commentaries And Criticismsmentioning
confidence: 99%
“…For instance, they review studies in which the triggering of motivated system defensiveness leads people to treat aspects of the societal status quo ('what is') as what is normatively right ('what ought to be')regardless of whether the status quo is congenial to selfand group-interest. Osborne et al (2019) discuss several ways in which system justification theory went beyond dominant paradigms in social psychology. They also point out that social systems are justified at multiple levels of analysis and suggest several ways in which the theory can contribute to an understanding of non-Western societies.…”
Section: Our Response To the Commentaries And Criticismsmentioning
confidence: 99%
See 1 more Smart Citation